Marketing Ethics & Society - Eagle, Lynne; Dahl, Stephan (London Sage Publications, 2015)
Taking a holistic and international perspective, this book critically examines the ethical challenges marketing faces and explores strategies marketers can use to respond to those challenges.
Keywords: Marketing social; Marketing -- Aspectos sociales; Marketing -- Aspectos éticos; Ética profesional